Rhodotorula Portillonensis Sp. Nov., a Basidiomycetous Yeast Isolated from Antarctic Shallow-Water Marine Sediment - Chavez-Rosales, R (2013)
During the characterization of the mycobiota associated with shallow-water marine environments from Antarctic sea, a novel pink yeast species was isolated. Sequence analysis of the D1/D2 domain of the LSU rDNA gene and 5.8S-ITS regions revealed that the isolated yeast was closely related to Rhodotorula pallida CBS 320T and Rhodotorula benthica CBS 9124T. On the basis of morphological, biochemical and physiological characterization and phylogenetic analyses, a novel basidiomycetous yeast species, Rhodotorula portillonensis sp. nov., is proposed. The type strain is Pi2T (=CBS 12733T =CECT 13081T) which was isolated from shallow-water marine sediment in Fildes Bay, King George Island, Antarctica. © 2013 IUMS.